Extraction, purification and antioxidant activity of novel polysaccharides from Dendrobium officinale by deep eutectic solvents. Issue 22 (17th November 2019) - Liang, Jing; Zeng, Yingjie; Wang, Hongfeng; Lou, Wenyong
Abstract: Two novel polysaccharides DOP1-DES and DOP2-DES with molecular weight of 297, 911 Da and 30, 400 Da were extracted by using DESs from Dendrobium officinale for the first time, and purified with macroporous resin AB-8, Sephadex G75 and Sephadex G200 chromatography. Besides, the effect of extraction temperature, molar ratio of DES, reaction time and compound enzymes concentration on the extraction yield of polysaccharides were investigated. Monosaccharide composition analysis showed DOP1-DES and DOP2-DES were composed of D-glucose and D-mannose with the ratio of 2.2:1 and 3.7:1, respectively. Structural features of DOP1-DES and DOP2-DES were investigated by a combination of FT-IR, methylation analysis and NMR, which indicated that both polysaccharides had a similarly backbone consisting of (1, 4)-linked β -D-Man p and (1, 4)-linked β -D-Glc p with different ratio. Simultaneously, the two fractions possessed considerable antioxidant activity. Abstract :